Array-based functional peptide screening and characterization of gold nanoparticle synthesis. (February 2017) - Tanaka, Masayoshi; Hikiba, Shun; Yamashita, Kiyoto; Muto, Masaki; Okochi, Mina
Graphical abstract: Abstract: Based on inorganic material production through biomineralization in organisms, the use of biological molecules in nanomaterial production has received increasing attention as a vehicle to synthesize inorganic materials with selected properties in ambient conditions. Among various biological molecules that interact with metallic surfaces, short peptides are putative ligand molecules as they exhibit potential to control the synthesis of nanoscale materials with tailored functions. Herein, using a spot synthesis-based peptide array, the gold nanoparticle (AuNP) binding activities of approximately 1800 peptides were evaluated and revealed various activities ranging from positive (high-affinity binding peptides) to negative (weak- or null-affinity binding peptides). Among 50 peptides showing the highest AuNP binding activity, 46 sequences showed the presence of tryptophan-based motifs including W[Xn ]W, H[Xn ]W, and W[Xn ]H (W: tryptophan, X: any amino acid, n: 1–8 amino acid residues), whereas none of these motifs was found in the WORST50 peptides. Notably, three peptides showing the highest binding affinities possessed bi-functionality in AuNP binding and Au(III) reduction in solution and on solid surfaces. In addition, the characterization of truncated peptide derivatives revealed unique peptide motifs for their function expressions that also supported the importance of tryptophan-based motifs for peptide-AuNP binding. These findings open the door for peptide-mediated precise regulation of AuNP synthesis in ambient condition and for site dependent controlled AuNP integration onto nanotechnological devices. Statement of Significance: The development of a technique for functionally regulated nanosized material production in ambient condition is broadly required according to the expansion of nanomaterial based applications. Short peptides, which bind to metallic surfaces, have great potential for the technique development, but the realization remains a difficult challenge due to the lack of metal binding peptide varieties. Herein, approximately 1800 peptides with the gold nanoparticle (AuNP) binding activity are reported and characterized. Furthermore, by three highest binding peptides, the expression of bi-functionality in AuNP binding and Au(III) reduction was serendipitously discovered in solution and on solid surfaces. These findings will be attributed to new technique development of functional nanoparticle synthesis in mild condition, and for site-dependent AuNP integration in various nanotechnological devices.